Perlindungan Data Pribadi Penyelenggaraan Fintech Lending Syariah : Analisis Teori Sistem Maqosid Syariah Jasser Auda - Ulum, Misbakhul; Suhendar, Heris (el hisbah Journal of Islamic Economic Law, 2023)
The presence of a Sharia fintech lending service platform provides various benefits to the community, with multiple conveniences offered. However, operationally, the implementation of Sharia fintech lending services can pose risks, leaks, or misuse of the personal data of service users. This is because the implementation of Sharia fintech lending cannot be separated from the activities of collecting, processing, using, and disclosing personal data of service users. This study analyzes the law on personal data protection in the implementation of Sharia fintech lending and its relevance to Jasser Auda's thoughts on the theory of systems in Maqashid Sharia. The research method uses normative law, which is prescriptive with a statute approach and conceptual. Primary and secondary legal sources are traced using document studies. The study results show that Sharia fintech lending organizers must protect the confidentiality of the personal data of service users and ensure the fulfillment of the rights of personal data owners. Personal data protection in Sharia fintech lending services is relevant to Auda's maqosid sharia system theory, especially the features of cognition, openness, interrelated hierarchy, and intentionality with the ultimate goal of fulfilling the principles of justice and the glorification of human rights. This study contributes to policy revisions to address the risks of implementing Sharia fintech lending more humanistic and equitable.